Barriers and facilitators to growth monitoring and promotion in Nepal: Household, health worker and female community health volunteer perceptions - Madeline M. Pollifrone; Kenda Cunningham; Pooja Pandey Rana; Morgan M. Philbin; Shraddha Manandhar; Krishna P. Lamsal; Raj Nandan Mandal; Vikash Deuja (Wiley, 2020)
Abstract Growth monitoring and promotion (GMP) is both a service for diagnosing inadequate child growth in its earliest stages and a delivery platform for nutrition counselling. The widespread use of GMP services in developing countries has the potential to substantially reduce persistent child undernutrition through early diagnosis and by linking caregivers and their children to key health and nutrition services. However, researchers have questioned the effectiveness of GMP services, which are frequently undermined by underdeveloped health systems and inconsistent implementation. This analysis examined both supply‐ and demand‐side factors for GMP utility in Nepal from the perspectives of beneficiaries and service providers, particularly focusing on three components of GMP: growth assessment, analysis of growth status and counselling. The most common factors influencing GMP uptake included beneficiaries' perceptions of the relative importance of GMP and the knowledge and skill of frontline workers. Both providers and beneficiaries viewed GMP as a secondary health and nutrition activity and therefore less important than curative services. We found deficits in GMP‐related knowledge and skills among providers (i.e. health workers and female community health volunteers), as well as indications of poor training quality and coverage. Furthermore, we found variation in GMP utilization by maternal age, education and residency (alone, nuclear or extended), as well as household socio‐economic well‐being and rurality. This study is the first to assess factors influencing both beneficiaries and service providers for GMP utilization. Further research is needed to explore the implementation of improved GMP protocols and to evaluate facility‐level implementation barriers.